Evaluasi Program Bersama Lindungi Anak (BERLIAN) Dalam Upaya Pencegahan Kekerasan Anak Pada Dinas Pemberdayaan Perempuan Perlindungan Anak Dan Keluarga Berencana di Kabupaten Sidoarjo - Augustika Wardani, Afiza; Dinda, Dinda Alfianingrum; Anugraha Dzaki, Adimas; Yahya Firmansyah, Fahmi; Arundinasari, Indira (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
The purpose of the study was to see how the Joint Program to Protect Children (Berlian) run by the Sidoarjo District Office of Women's Empowerment, Child Protection, and Family Planning. The study method used is the CIPP model evaluation research method which includes context, input, process and product. Interviews, observations and written notes were some of the ways primary and secondary data sources were used to gather information, knowledge and data on how the Joint Program to Protect Children (Berlian) was used. The data came from policy reviewers in Sidoarjo district who work in family planning, child safety and women's empowerment services. The data also came from teachers at SMPN 1 Wonoayu and SMPN 1 Krembung. Context, input, process and product variables are the four categories on which the research findings are based. The research findings show that while the assessment of input variables is considered highly effective, the assessment of context variables is broadly considered ineffective, the assessment of process variables still requires work, and the assessment of product variables is considered effective.